Language–Subject Teacher Collaboration in English-Medium Higher Education: Current Practices and Future Possibilities - Malmström, Hans; Zhou, Sihan (RELC journal, 2025)
The collaborative competence of subject (discipline) teachers and language (English for academic or specific purposes) teachers in higher education is a central concern in English-medium instruction contexts, where they frequently interact. This brief scoping review provides a snapshot of the current state of English-medium instruction teacher collaboration and guides collaborative practice to better support language teachers, subject teachers and (ultimately) students. The review is restricted to empirical studies and focuses on the forms of teacher collaboration, barriers to collaboration, and strategies to overcome these challenges. Teacher collaborations occur at institutional, departmental and individual levels, and, at each level, some obstacles limit the effectiveness and sustainability of collaborations. Proposed solutions range from individual initiatives to systematic institutional support. Based on these findings, the paper concludes with practical recommendations to enhance future collaborations.